The interaction between oral microbiota and gut microbiota in atherosclerosis - Li, Xinsi; Li, Qian; Wang, Li; Ding, Huifen; Wang, Yizhong; Liu, Yunfei; Gong, Ting (Frontiers in Cardiovascular Medicine, 2024)
Atherosclerosis (AS) is a complex disease caused by multiple pathological factors threatening human health-the pathogenesis is yet to be fully elucidated. In recent years, studies have exhibited that the onset of AS is closely involved with oral and gut microbiota, which may initiate or worsen atherosclerotic processes through several mechanisms. As for how the two microbiomes affect AS, existing mechanisms include invading plaque, producing active metabolites, releasing lipopolysaccharide (LPS), and inducing elevated levels of inflammatory mediators. Considering the possible profound connection between oral and gut microbiota, the effect of the interaction between the two microbiomes on the initiation and progression of AS has been investigated. Findings are oral microbiota can lead to gut dysbiosis, and exacerbate intestinal inflammation. Nevertheless, relevant research is not commendably refined and a concrete review is needed. Hence, in this review, we summarize the most recent mechanisms of the oral microbiota and gut microbiota on AS, illustrate an overview of the current clinical and epidemiological evidence to support the bidirectional connection between the two microbiomes and AS.